Power, luck and freedom : Collected essays - Dowding, Keith M. (Book collections on Project MUSE., 2016)
Keith Dowding is a major figure in relation to debates on power and highly influential in the fields of political theory and political science. Power luck and freedom is a collection of his essays and articles, that provide a significant reference point for the field of power analysis.